From Clicks to Conversations: The Evolution of Chatbot Marketing - Hendro Sugiarto; Desi Try Anggarini; Lati Sari Dewi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research investigates the dynamics of chatbot marketing within PT Sinar Sosro, focusing on the interplay between user experience, marketing strategy evolution, and the effectiveness of chatbot conversations. Through a quantitative approach utilizing Smart PLS analysis, data was gathered from a sample of 100 consumers. The findings reveal significant direct effects of both user experience and marketing strategy evolution on chatbot conversations, emphasizing their pivotal roles in driving meaningful engagements. Moreover, indirect effects analysis highlights the mediating role of user experience in the relationship between marketing strategy evolution / Number of Clicks and chatbot conversations. These insights underscore the importance of optimizing user-centric approaches and aligning marketing strategies with user preferences to foster positive experiences, enhance chatbot effectiveness, and achieve marketing objectives effectively within PT Sinar Sosro's digital ecosystem.